Culinary Tourism Location Search Application Using Location Based Service Method In Jakarta City Area Based On Android - Bella Risky Nasution; Rahmawati Febrifyaning Tias; Fardanto Setyatama; Mas Nurul Hamidah (JEECS (Journal of Electrical Engineering and Computer Sciences), 2022)
Culinary diversity causes many types of restaurants and cafes in the city of Jakarta. The increasing number of culinarylocations makes it difficult for culinary connoisseurs to find locations and restaurants that match what they want.Therefore we need an application that has functional aspects in finding culinary locations. The application of the LocationBased Service (LBS) method in this application can help users to find the nearest culinary so that users can choose aculinary place that is closest to their location. Applications created using Android Studio with the Zomato API can makeit easier for people to find culinary locations around the city of Jakarta. By using Android mobile technology as anothermedium, people don't have to ask other people to find culinary spots. The program is tested to find out possible errors,this test uses Black Box testing and User Testing. Application testing to find culinary places in the city of Jakarta candisplay detailed information on the restaurants selected by the user and the test results are as expected.